PEMUNGUTAN PAJAK DAERAH DALAM RANGKA MENINGKATKAN PENDAPATAN ASLI DAERAH - Eko Cahyo Mayndarto (Jurnal Manajemen FE-UB, 2014)
Alongwithregional autonomy, haschanged theparadigmof governancemureas-wherepoweris centralizedto a decentralizedchangehy providingthe broadest possihleautonomyas stipulated inLaw No.22 of 1999on Regional Governmenthereinafier referredto a.sAct.No.22/1999, laterreplacedhyAct No.32 of 2004hereinafter referredto usActNo.32/2004 Changes inthe areaof governmentre;•ulatory policiesare alignedwith thepolicy change•totaxe.sund leviesas- the fiundationlor the regionin exploringthe potential oflocal revenue, e.specially revenue.It is characterized hychanges tothe 1,awlVo.18 Year1987 onRegional Taxesand Leviesby ActNo. 34 of 2000 onthe Amendmentof LawNumher 18Year1987 onRegional Taxesand Levies, hereinafter referredlo asActNo..34/2000.   Inthisjournal, formulateihe prohlemabout, What aboutlocaltax collection order to increaserevenue? ArePublic Sectoraccountinghas a close connectionwiththe applicationandthe accounting treatmentin the public domain? Doesrevenuederivedfromthe abovesourcesof revenuerecelpisobtathedandextradedfrom thenativewealth?   Low No.28 of 2009 onregional taxesand had arrungedit ckar thattobeleviedonan area, anykindof local taxesto be selbylocal regulation. It ismeanttobe appliedandcollectedatthe provincial, clislrict, orcity, must firstsek‘ locul regulationsonthelocal taxe•. Local regulations onalocal taxwas enactedin thesheetareaconcerned.   Keywords: Collection of Local Taxes, Local Revenue